Cultivating Eco-Literate Writers: Exploring the Intersection of Environmental Awareness and Text-Based Writing Skills - Isnanda, Romi; Ramadhan, Syahrul; Hayati, Yenni (Journal of Teaching and Learning, 2025)
Expanding information related to environmental degradation is one potential approach to enhance students' environmental literacy and awareness (eco-literate). This research investigates the relationship between students' skills in writing popular text-based articles and their ecological literacy. A quasi-experimental research design was employed with a one-group test. The sample consisted of 23 Indonesian Language and Literature Education Program students, selected through purposive sampling. Data collected included scores on writing assignments of popular articles and questionnaire results regarding students' knowledge of ecological literacy. Data analysis techniques involved testing for correlation, regression, normality, multicollinearity, heteroskedasticity, F-test, and t-test. Pearson correlation results showed a significant relationship between students' eco-literate knowledge and their ability to write popular articles, with a coefficient of determination of 55.4%, indicating that 55.4% of the variation in the ability to write articles can be explained by eco-literate knowledge. The regression analysis revealed a strong correlation coefficient of 0.942, indicating a very strong relationship between various aspects of eco-literate knowledge and students' ability to write popular articles. The t-test further demonstrated that environmental concern is the factor that has the most significant influence on students' writing ability, with a regression coefficient (b2) of 1.793.